Pengaruh Brand Ambassador dan Konten Marketing Terhadap Keputusan Pembelian Brand Jiniso pada Platform Tiktok - Aldy Renaldy (JURNAL RISET MANAJEMEN (JURMA), 2024)
The purpose of this research is to find out the influence of Brand Ambassadors and Marketing Content on Jiniso Brand Purchase Decisions on the Tik Tok Platform. This kind of research is quantitative. There were 150 respondents in this research population. Questionnaires were distributed as part of the data collection strategy. Linear regression analysis was used to test this hypothesis. The tik tok platform is the subject of this research. The results of this research show that. 1) shows that the significance level for the Brand Ambassador variable is 0.008 < 0.05, meaning it is significant while the ttable value can be calculated with α = 0.05 and df = 147 can be calculated with a table of 1,976. tcount > ttable (9.917 > 1.976). So, it can be concluded that Ho is rejected and Ha is accepted, which means that Brand Ambassador and Marketing Content have a positive influence on Jiniso Brand Purchase Decisions. 2) shows that the level of significance for the Marketing Content variable is 0.003 < 0.05, meaning it is significant, while the ttable value can be calculated with α = 0.05 and df = 147 and a table of 1,976 can be obtained. tcount > ttable (7.358 > 1.976). So, it can be concluded that Ho is rejected and Ha is accepted, which means it is positive for the Jiniso Brand Purchase Decision. 3) The calculated F value obtained is 50,579 > 3.06 and the significance is 0.000 < 0.05. This indicates that the fcount value is greater than the ftable and sig values. smaller than 0.05. So it can be concluded that Ho is rejected and Ha is accepted, meaning that the implementation of Brand Ambassador and Marketing Content simultaneously has a positive effect on Jiniso Customer Purchasing Decisions.